2016
DOI: 10.5194/acp-16-7709-2016
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of biomass-burning aerosol size distributions due to coagulation: dependence on fire and meteorological details and parameterization

Abstract: Abstract. Biomass-burning aerosols have a significant effect on global and regional aerosol climate forcings. To model the magnitude of these effects accurately requires knowledge of the size distribution of the emitted and evolving aerosol particles. Current biomass-burning inventories do not include size distributions, and global and regional models generally assume a fixed size distribution from all biomass-burning emissions. However, biomass-burning size distributions evolve in the plume due to coagulation… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
72
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(79 citation statements)
references
References 55 publications
6
72
1
Order By: Relevance
“…Coagulation also shifts D g to larger values (through coagulational growth) and narrows the size distribution, decreasing σ g , by removing smaller particles (Sakamoto et al, ). Figure shows that for CoagOn cases, this coagulational increase in D g is most evident in larger (1 km 2 and greater) fire sizes, with increases up to a D g of 200 nm from coagulation alone.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Coagulation also shifts D g to larger values (through coagulational growth) and narrows the size distribution, decreasing σ g , by removing smaller particles (Sakamoto et al, ). Figure shows that for CoagOn cases, this coagulational increase in D g is most evident in larger (1 km 2 and greater) fire sizes, with increases up to a D g of 200 nm from coagulation alone.…”
Section: Resultsmentioning
confidence: 99%
“…Figure shows that for CoagOn cases, this coagulational increase in D g is most evident in larger (1 km 2 and greater) fire sizes, with increases up to a D g of 200 nm from coagulation alone. As discussed in section , coagulation rates are proportional to the square of the number concentration, and thus, the coagulation‐caused increase in D g amplifies with increasing fire sizes that take longer to dilute as well as for fires with higher emission fluxes leading to higher initial concentrations (Sakamoto et al, ). Additionally, decreasing dilution rates through a more‐stable atmosphere for a given smoke emission flux and size will also amplify the coagulational effect on D g (section S5 and Figures S20 and S22).…”
Section: Resultsmentioning
confidence: 99%
“…The D VED_mode of rBC distributions were approximately 180 nm in the evening and at night on low‐fog days and approximately 140 nm on high‐fog days. On high‐fog days the mean temperatures (12 °C) are higher than low‐fog days (6 °C), suggesting that residential wood burning activity might have been lower resulting in lower mass flux and smaller D VED_mode on high‐fog days because the fractional contribution of wood burning‐derived rBC mass was lower (Sakamoto et al, ). In the morning and afternoon of low‐fog days, rBC mass distributions have broader peaks and D VED_mode at 140 nm, while the D VED_mode of rBC mass distribution on high‐fog days appears to be below the detection range of the SP2 (80 nm diameter).…”
Section: Resultsmentioning
confidence: 99%
“…This methodology does not provide information about smoke concentration (µg m −3 ), and we have not placed additional altitude constraints on the trajectories. A further weakness of smoke hours is that they have no way of accounting for secondary organic aerosol particle formation, which previous studies have shown can be significant (e.g., Janhäll et al, 2010;Sakamoto et al, 2015Sakamoto et al, , 2016. However, these processes remain poorly understood and represented in chemical transport models, so an appreciation for the fact that these processes exist, but not attempting to account for them, is sufficient for understanding the results presented in this work.…”
Section: Combined Analysis Of Hysplit Points and Forward Trajectoriesmentioning
confidence: 93%